Investigating the role of commercialization on purchase intention - Naser Azad; Maryam Safaee; Mahdieh Shahrabi Farahani (Management Science Letters)
This paper presents a study to determine the role of commercialization on purchase intention in auto industry. The study designs a questionnaire in Likert scale and distributes it among some randomly selected people who lived in city of Tehran, Iran. The study investigates the effects of four factors including competitive condition, product development strategy, competitive advantage and economic growth on customers’ intention to purchase. Using structural equation modeling the study has determined a positive and meaningful relationship between each four components and purchase intention. In our study, the highest impact belongs to competitive condition followed by product development strategy.